PENGARUH INTENSITAS PENGGUNAAN GADGET TERHADAP TINGKAT KEBUGARAN JASMANI SISWA PROGRAM ASISTEN KEPERAWATAN - Tini Martini; R. Dadan Pra Rudiana; Ine Anggraini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The development of digital technology has increased gadget use among adolescents, including vocational high school (SMK) students. Excessive gadget use can trigger sedentary behavior, potentially reducing physical activity and impacting physical fitness levels. This condition is of particular concern for students in health expertise programs, such as the Nursing Assistant Program, who require good physical condition to support future healthcare activities. This study aims to analyze the effect of gadget use intensity on the physical fitness levels of students in the Nursing Assistant Program at SMK Kesehatan Bhakti Kencana Subang. This study used a quantitative approach with a correlational method. The study population was all 267 students in the Nursing Assistant Program. The study sample of 160 students was determined using the Slovin formula with a 5% margin of error and selected using a proportional random sampling technique. Data on gadget use intensity were collected through a questionnaire, while physical fitness levels were measured using the Indonesian Physical Fitness Test (TKJI). Data analysis was performed using simple linear regression with the assistance of SPSS software. The results of the study indicate that the intensity of gadget use has a significant effect on students' physical fitness levels with a regression equation of and a significance value of 0.000 (p < 0.05). The coefficient of determination value indicates that the intensity of gadget use contributes 10.4% to students' physical fitness levels. This finding indicates that the higher the intensity of gadget use, the lower the students' physical fitness levels tend to be. Therefore, efforts are needed to control gadget use and increase students' physical activity to maintain physical fitness, especially for students who are prepared for professions in the health sector. ABSTRAK Perkembangan teknologi digital telah meningkatkan penggunaan gadget di kalangan remaja, termasuk siswa sekolah menengah kejuruan (SMK). Penggunaan gadget yang berlebihan dapat memicu perilaku sedentary yang berpotensi menurunkan aktivitas fisik serta berdampak pada tingkat kebugaran jasmani. Kondisi ini menjadi perhatian khusus bagi siswa program keahlian di bidang kesehatan, seperti Program Asisten Keperawatan, yang memerlukan kondisi fisik yang baik untuk mendukung aktivitas pelayanan kesehatan di masa depan. Penelitian ini bertujuan untuk menganalisis pengaruh intensitas penggunaan gadget terhadap tingkat kebugaran jasmani siswa Program Asisten Keperawatan di SMK Kesehatan Bhakti Kencana Subang. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Populasi penelitian adalah seluruh siswa Program Asisten Keperawatan yang berjumlah 267 siswa. Sampel penelitian sebanyak 160 siswa ditentukan menggunakan rumus Slovin dengan tingkat kesalahan 5% dan dipilih menggunakan teknik proportional random sampling. Data intensitas penggunaan gadget dikumpulkan melalui kuesioner, sedangkan tingkat kebugaran jasmani diukur menggunakan Tes Kebugaran Jasmani Indonesia (TKJI). Analisis data dilakukan menggunakan regresi linear sederhana dengan bantuan perangkat lunak SPSS. Hasil penelitian menunjukkan bahwa intensitas penggunaan gadget berpengaruh signifikan terhadap tingkat kebugaran jasmani siswa dengan persamaan regresi dan nilai signifikansi sebesar 0.000 (p < 0.05). Nilai koefisien determinasi menunjukkan bahwa intensitas penggunaan gadget memberikan kontribusi sebesar 10.4% terhadap tingkat kebugaran jasmani siswa. Temuan ini menunjukkan bahwa semakin tinggi intensitas penggunaan gadget maka tingkat kebugaran jasmani siswa cenderung menurun. Oleh karena itu, diperlukan upaya untuk mengontrol penggunaan gadget serta meningkatkan aktivitas fisik siswa guna menjaga kebugaran jasmani, khususnya bagi siswa yang dipersiapkan untuk profesi di bidang kesehatan.